Pigmented villonodular synovitis of the temporomandibular joint: CT imaging findings - Le, Wei-Jie; Li, Ming-Hua; Yu, Qiang; Shi, Hui-Min (Clinical imaging, 2014)
The purpose of this study was to determine the characteristic computed tomography (CT) findings of pigmented villonodular synovitis (PVNS) of the temporomandibular joint (TMJ). Eight subjects with PVNS were examined with both pre and post contrast CT scans. All lesions were histopathologically confirmed through surgery. CT appearances of the lesions were reviewed. Among the eight subjects, 8 (100%) demonstrated soft tissue mass and enhancement after contrast administration, 6 (75%) appeared as all or focal areas of noncontrast hyperdensity, 6 (75%) had widening of the joint spaces. Bony erosion of the mandibular condyles and articular surfaces were found in 7 (87.5%) and 6 (75%) subjects, respectively. Based on the CT findings, PVNS of the TMJ is characterized by hyperdensity soft tissue mass and further increase in density after contrast administration, bony destruction of the mandibular condyles and skull base, and intracranial extension.